Whispers and Reflections: The Phenomenon of the Double in "William Wilson" by E.A. Poe - Gerardo Argüelles Fernández; Luz del Carmen Ledesma Juárez (Estudios de Teoría Literaria, 2023)
If an intuitive hypothesis indicates that 90% of the literary characters undergo extraordinary states of mind, in this contribution we pretend to inquire about an alternative to the medical sciences of behavior, in order to provide interpretative clarity concerning the poetological consequences at this radical experience of subjectivity. In this sense, we present a study regarding the amplitude and limitations on the approach towards the double motif of the double, having as basis the short story “William Willson” [1839] by E.A. Poe, for the sake of contextualizing the implicit difficulty in the phenomenon of the autoscopic depersonalization taken to literature, starting with the Anglo-Saxon Gothic up to the end of the xix century at least. Secondly, we offer some suggestions for analysis in order to take up this interpretative challenge presented by the american author, who never ceases to capture our attention as a great weaver of warps whose literary proposal refuses to be reduced to a mere psychological assessment.